Die Psalmen als „verbale Bühnen“: ein experimenteller Blick auf die dramatisch-performativen Strukturen der Psalmen - Hopf, Matthias (Biblische Zeitschrift, 2021)
Many psalms display characteristics that are – in literary theory – associated with performance texts like “dramas”. The criteria for this are that texts feature a “lexis” (direct speech out of the mouth of a discernible character), an “opsis” (elements evoking a scenery etc., often presented in direct speech), and plot structures (not only story plots, but also character development and the like). Many psalms fit this criterology, even though some more than others, as well as partially with some very unique characteristics. Still, this allows for understanding several psalms as miniature “verbally presented stages”. The implications of this basal communicative structure are explored in this contribution, a major of which pertains to the recent discussion on identification potentials: In some psalms the lyrical subject is an offer to identify with, whereas in others – the ones discussed here – it is better understood as opposite to the recipient.